Augmented Reality-Based Surgery on the Human Cadaver Using a New Generation of Optical Head-Mounted Displays: Development and Feasibility Study - Behrus Puladi; Mark Ooms; Martin Bellgardt; Mark Cesov; Myriam Lipprandt; Stefan Raith; Florian Peters; Stephan Christian Möhlhenrich; Andreas Prescher; Frank Hölzle; Torsten Wolfgang Kuhlen; Ali Modabber (JMIR Publications, 2022)
BackgroundAlthough nearly one-third of the world's disease burden requires surgical care, only a small proportion of digital health applications are directly used in the surgical field. In the coming decades, the application of augmented reality (AR) with a new generation of optical-see-through head-mounted displays (OST-HMDs) like the HoloLens (Microsoft Corp) has the potential to bring digital health into the surgical field. However, for the application to be performed on a living person, proof of performance must first be provided due to regulatory requirements. In this regard, cadaver studies could provide initial evidence. ObjectiveThe goal of the research was to develop an open-source system for AR-based surgery on human cadavers using freely available technologies. MethodsWe tested our system using an easy-to-understand scenario in which fractured zygomatic arches of the face had to be repositioned with visual and auditory feedback to the investigators using a HoloLens. Results were verified with postoperative imaging and assessed in a blinded fashion by 2 investigators. The developed system and scenario were qualitatively evaluated by consensus interview and individual questionnaires. ResultsThe development and implementation of our system was feasible and could be realized in the course of a cadaver study. The AR system was found helpful by the investigators for spatial perception in addition to the combination of visual as well as auditory feedback. The surgical end point could be determined metrically as well as by assessment. ConclusionsThe development and application of an AR-based surgical system using freely available technologies to perform OST-HMD-guided surgical procedures in cadavers is feasible. Cadaver studies are suitable for OST-HMD-guided interventions to measure a surgical end point and provide an initial data foundation for future clinical trials. The availability of free systems for researchers could be helpful for a possible translation process from digital health to AR-based surgery using OST-HMDs in the operating theater via cadaver studies.